Publics à l’œuvre. Créer à l’ère des médias praticables et des images interactives - Jean-Paul Fourmentraux (Images Re-Vues)
The artistic work dedicated to the Internet joins the creation of interactive artworks to the production of forms of communication and of exhibition which aim to involve the public and make it loyal. This article analyses these new artistic figures and their relational modes in a context where the transformation into artworks cannot be dissociated from the reception of evolutionary and porous contents. The experience of media is there less strictly distributed between emission and reception, conceived as two successive events of a fixed and immutable message. Where the work now materialises a “field of possibles”, experimentation takes over the traditionally rigid logic of transmission of informational contents. This article, at the intersection of the sociology of uses and of artistic innovation, offers a description of these relations between settings and practices and puts into perspective some forms of attachment still specific to this art but revealing new mediatic regimes.